EXTENDING THE CONCEPT LEARNING STATAGEY TO INCREASE THE STUDENTS’ READING COMPREHENSION AND THEIR SELF-DETERMINATION - Apriana; Lesi Anggraini (Universitas PGRI Palembang, 2023)
This study set intended to determine whether or not students' reading comprehension may be improved by using the concept learning method technique. This study used a mixed method of methodology. Triangulation—questionnaires, interviews, and documentation—was used as a data collection method. The author employed data reduction, display data, and conclusion or verification data to analyze the data. Based on the conducted research, the study's conclusion was: (1) Based on the results of the questionnaire and interview, it can be concluded that using the Concept Learning Strategy technique in the learning process was beneficial. When studying reading comprehension, the idea learning strategy technique is more effective than the traditional teaching approach. Furthermore, there existed a discrepancy in the reading proficiency of students instructed through the concept learning strategy approach when analyzed from the perspective of self-determination. Additionally, there existed a relationship between the concept learning strategy approach and self-determination concerning students' reading comprehension when teaching reading comprehension skills through the principled learning strategy.